2023
DOI: 10.1039/d2mh01429g
|View full text |Cite
|
Sign up to set email alerts
|

Linear optical afterglow and nonlinear optical harmonic generation from chiral tin(iv) halides: the role of lattice distortions

Abstract: The striking chemical variability of hybrid organic-inorganic metal halides (HOMHs) accords them fascinating optoelectronic properties. The inorganic skeletons of HOMHs are often flexible and their lattice deformations could serve as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 107 publications
0
12
1
Order By: Relevance
“…In 3a). These values are higher than those of previously reported NLO organic-inorganic halides, including (H 7 C 3 N 6 )(H 6 C 3 N 6 )HgCl 3 (225 °C), 16 (CH 3 NH 3 )GeBr 3 (500 K), 30 67 and (CH 3 NH 3 )GeBr 3 (2.91 eV). 30…”
Section: Structural Comparisoncontrasting
confidence: 58%
“…In 3a). These values are higher than those of previously reported NLO organic-inorganic halides, including (H 7 C 3 N 6 )(H 6 C 3 N 6 )HgCl 3 (225 °C), 16 (CH 3 NH 3 )GeBr 3 (500 K), 30 67 and (CH 3 NH 3 )GeBr 3 (2.91 eV). 30…”
Section: Structural Comparisoncontrasting
confidence: 58%
“…In the process of excited state recombination, a higher degree of lattice distortion will increase the nonradiative loss of excitation energy, thus effective quenching of luminescence, and vice versa. [ 41–43 ] Hence, the Sb 3+ −1 with the maximum distortion degree exhibits negligible emission, while Sb 3+ −2α and Sb 3+ −2β with moderate lattice distortion exhibit an efficient emission. Recently, many studies have shown that the large distance of M–M (M = Pb 2+ , Sn 2+ , Mn 2+ , Sb 3+ , Bi 3+ ) will increase the PLQY, which should be attributed to the inhibition of concentration quenching.…”
Section: Resultsmentioning
confidence: 99%
“…Switchable materials are substances that can switch between two different states under external stimuli such as heat, light, external electric field, and magnetic fields; their physical properties change with the change of states. These materials can be widely used in various fields such as communication transmission, information storage, and photonic carriers. Dielectric switches are mostly appearing in structural phase transition materials, where the dielectric constant changes abruptly near the phase transition temperature ( T h ) and reversible cycling occurs. For example, (DMTBA) 3 Bi 2 Br 9 (DMTBA = N , N -dimethyl- tert -butylaminiu) was reported to have a pair of reversible phase transitions at 188 and 425 K and exhibited excellent dielectric switching properties However, a single dielectric switch also limits the application scenarios for the material.…”
Section: Introductionmentioning
confidence: 99%